North Star Facilitator's Manual - Manke, Nancy; Matheny, Karla; De Barbieri, Patricia (s.n., 2004)
A program for school-age girls designed to promote social and emotional learning, to enhance resiliency, improve self confidence and aid in the prevention of future problems such as eating disorders, drug abuse and poor academic performance. - p. [1]
Keywords: Self-esteem in women; Study and teaching; Study and teaching; Self-esteem in children; dept.mft; faculty_collection